2021
DOI: 10.3389/fonc.2021.710899
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neural Microenvironment in Prostate Cancer in Context of Neural Density, Perineural Invasion, and Neuroendocrine Profile of Tumors

Abstract: BackgroundCancer stroma contains the neural compartment with specific components and action. Neural microenvironment processing includes among others axonogenesis, perineural invasion (PNI), neurosignaling, and tumor cell neural/neuroendocrine differentiation. Growing data suggest that tumor-neural crosstalk plays an important function in prostate cancer (PCa) biology. However, the mechanisms involved in PNI and axonogenesis, as well as their patho-clinical correlations in this tumor are unclear.MethodsThe pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 97 publications
6
17
0
Order By: Relevance
“…However, few studies have focussed on whether there is an association between biopsy PNI and PSM. Positive resection after radical prostate cancer affects the survival and prognosis of patients and has paid attention to the majority of urosurgeons (Sigorski et al, 2021). At present, some researchers believe that tumour stage and pathological characteristics are related to positive margin after radical prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have focussed on whether there is an association between biopsy PNI and PSM. Positive resection after radical prostate cancer affects the survival and prognosis of patients and has paid attention to the majority of urosurgeons (Sigorski et al, 2021). At present, some researchers believe that tumour stage and pathological characteristics are related to positive margin after radical prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focussed on whether there is an association between biopsy PNI and PSM. Positive resection after radical prostate cancer affects the survival and prognosis of patients and has paid attention to the majority of urosurgeons (Sigorski et al, 2021). At present, some researchers believe that tumour stage and pathological character- Gleason pattern 4 (poorly formed, fused glands, glomerulation, and cribriform types) prostate cancer according to the ISUP 2014 modified Gleason system, and Flammia et al (Flammia et al, 2020) found that cribriform pattern was significantly and inversely correlated with PNI but not with other pathological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[133] In cancer research this biomarker have shown to be useful to visualize PNI and quantitate neural structures in primary melanoma and prostate cancer (Figure 3). [134,135]…”
Section: Neurofilamentmentioning
confidence: 99%
“…This biomarker has being used as a marker of neural and neuroectodermal tumors, to study nerve regeneration in skin samples with herpes virus infection, and to study PNI and nerve density in pancreatic and prostate cancer. [135,[137][138][139]…”
Section: Pgp95mentioning
confidence: 99%
“…Our group found that PCa innervation was higher on the proximal cancer surroundings than within PCa. Moreover, sympathetic ND was lower in PCa than in non-neoplastic prostate [ 5 ].…”
mentioning
confidence: 99%